Utilization of kitchen ingredients in efforts to increase productivity and immune system - Mayang Murni; Asnidar Asnidar; Rizky Nafaida (Universitas Muhammadiyah Magelang, 2023)
Changes in temperature and extreme weather conditions, combined with exposure to pollution, have a negative impact on the body's immunity. This poses a challenge for every mother, who typically acts as a shield for her family in maintaining their immune system. Instead of using chemical-based multivitamins that may have long-term effects, there are kitchen ingredients that can be utilized to create natural multivitamins. The purpose of this program is to enhance the knowledge, skills, and productivity of partners in processing kitchen ingredients into natural, healthy beverages using the JSR (Prophet's Healthy Technique) method. The program begins with providing awareness sessions to partners, who are members of the PKK Sungai Pauh Firdaus, followed by training in the processing of kitchen ingredients into healthy beverages using the more practical JSR method, which also allows for selling and adds economic value for partners. The results obtained by partners after participating in the program include an improvement in their knowledge and skills in processing kitchen ingredients into healthy beverages. There has also been an increase in economic productivity among partners, including orders for healthy beverages from members of the DWP social gathering organized by one of the PKK Sungai Pauh Firdaus members.